Anne Frank The Diary Of A Young Girl - Frank, Anne (New Rochelle, NY Spoken Arts, 1993)
A thirteen-year-old Dutch-Jewish girl records her impressions of the two years she and seven others spent hiding from the Nazis before they were discovered and taken to concentration camps. Includes entries previously omitted.
Keywords: Frank, Anne, -- 1929-1945 -- Diaries. Holocaust, Jewish (1939-1945) -- Netherlands -- Amsterdam -- Personal narratives. Jews -- Persecutions -- Netherlands -- Amsterdam